2018
DOI: 10.1093/pubmed/fdy121
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index, waist circumference, waist–hip ratio and cognitive disorder in older adults

Abstract: BMI obesity and WC/WHR central obesity have a combined effect on cognitive impairment and WHR has a stronger association with cognitive impairment than WC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 13 publications
3
41
1
Order By: Relevance
“…Another finding of the present study is that abdominal obesity is associated with an increased risk of cognitive impairment. Liu et al showed that central obesity (defined by WHR <0.9 for males and <0.85 for females) was significantly associated with a higher risk of cognitive impairment in 491 subjects aged 70 years and older (OR=1.980, 95% CI=1.129–3.472) 20. Luchsinger et al revealed that a higher WHR was related to a higher risk of late-onset Alzheimer’s disease (HR of the fourth quartile compared to the first=2.5, 95% CI=1.3–4.7) after adjustment for conventional risk factors 21.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of the present study is that abdominal obesity is associated with an increased risk of cognitive impairment. Liu et al showed that central obesity (defined by WHR <0.9 for males and <0.85 for females) was significantly associated with a higher risk of cognitive impairment in 491 subjects aged 70 years and older (OR=1.980, 95% CI=1.129–3.472) 20. Luchsinger et al revealed that a higher WHR was related to a higher risk of late-onset Alzheimer’s disease (HR of the fourth quartile compared to the first=2.5, 95% CI=1.3–4.7) after adjustment for conventional risk factors 21.…”
Section: Discussionmentioning
confidence: 99%
“…At study entry and annually, we measured BP, BMI, waist‐hip ratio (WHR), and depressive symptoms using the modified Center for Epidemiologic Studies Depression scale (mCES‐D) . Consenting participants provided blood samples for APOE genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Because these two parameters were associated with cognition and balance [26,27] , so BMI and abdominal circumference were used as covariates in the statistical analysis. By adjusting the covariates of BMI and abdominal circumference, the data of postural and cognitive performance in the single or dual tasks were assessed using a mixed model analysis of covariance.…”
Section: Discussionmentioning
confidence: 99%